Baking : breads, muffins, cakes, pies, tarts, cookies and bars - Day, Martha (Lorenz Books, 2010)
Includes over 400 recipes featuring delectable homemade breads, pies, tarts, muffins, cookies and cakes, including a selection of low fat recipes. This title offers a comprehensive look at breads - from everyday loaves to classic international specialities